A comprehensive review of AI-based collagen valorization: Recent trends, innovations in extraction, and applications - Arthi Srinivasan; Arun Gupta; Vigneswaran Narayanamurthy (Green Analytical Chemistry)
Collagen, constituting approximately 30 % of total body proteins, is a critical structural protein with extensive applications in biomedical, cosmetic, and food industries. Despite its importance, large volumes of collagen-rich organic waste generated by meat, leather, and seafood industries remain underutilized, leading to significant environmental challenges. Piscine waste contributes up to 70 % of total fish body weight, while poultry farms produce approximately 89,000 tons of solid waste annually. This review provides a detailed analysis of collagen-rich waste sources, including bovine, porcine, piscine, caprine, ovine, and avian, examining their waste percentages, protein content, and extraction efficiencies. The study explores the transformative role of artificial intelligence (AI) in optimizing collagen extraction processes, enhancing efficiency, yield, and quality while reducing energy consumption and waste generation. AI-driven methods have demonstrated improvements in energy efficiency by up to 40 % and reductions in waste by 45 %, enabling environmentally sustainable and cost-effective practices. Collagen valorization is further aligned with circular economy principles, focusing on converting waste into high-value products such as collagen peptides, biomaterials, and functional foods. By integrating advanced AI technologies with diverse collagen sources, this review provides a comprehensive framework for sustainable collagen processing that addresses environmental challenges and enhances resource utilization. The study emphasizes the potential to create economically valuable products while promoting environmental sustainability and innovation, paving the way for efficient and eco-friendly practices in the collagen industry through a holistic and multidisciplinary approach.